Sustainable inventory model with environmental factors using permissible delay in payments - Nalini S.; Ritha W (The Scientific Temper, 2025)
Provision of permissible delay in payments is a good business tactic resorted to in almost all types of businesses. Such a practice also exists in inventory management companies. Many articles have been presented on the subject of permissible delay in payments within the economic order quantity (EOQ) framework with the ultimate aim of minimizing total cost. In general, such articles focused on the supplier offering the retailer a fully permissible delay in payments only if a certain minimum quantity (as specified by the supplier) is ordered. A variation in the above idea has been used to develop a model with the objective of a cost minimization problem to determine the retailers’ optimal inventory cycle time and optimal order quantity. The objective of this paper is to analyze the abovementioned model in detail and provide use case scenarios in which the effect of the variation of quantity of selected variables on the cycle time and the optimal order quantity are presented. The effect of these variables on the optimum and transportation costs is also analyzed. Finally, improvements in the existing model have been suggested with numerical examples for more clarity.